2016
DOI: 10.7819/rbgn.v18i61.2845
|View full text |Cite
|
Sign up to set email alerts
|

The role of financial media in share repurchases

Abstract: Purpose -This paper examines the impact that financial media coverage has on share repurchase outcomes in the U.S.Design/methodology/approach -I perform regression analysis to examine how the volume of firm-specific news articles about the announcements relates to firms' decisions to actually repurchase shares following those announcements. I also examine the role of media in the firms' long-term post-announcements stock performances. To alleviate concerns about confounding effects that can simultaneously driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The applications of TRNA news data set to financial research has recently gained interest. Cahill et al (), Pinto‐Gutierrez (), Allen et al (2016), Hendershott et al (), Li et al (2015), Smales (), Uhl (), and Groß‐Klußmann and Hautsch () have variously shown the usefulness of the TRNA data set in stock markets and in commodity markets.…”
mentioning
confidence: 99%
“…The applications of TRNA news data set to financial research has recently gained interest. Cahill et al (), Pinto‐Gutierrez (), Allen et al (2016), Hendershott et al (), Li et al (2015), Smales (), Uhl (), and Groß‐Klußmann and Hautsch () have variously shown the usefulness of the TRNA data set in stock markets and in commodity markets.…”
mentioning
confidence: 99%